Training of Trainers (ToT) Workshop on Soil Nutrient and Water Management in Crop Production Course Module - Ekepu, David; Majaliwa, Jackson Gilbert Mwanjalolo; Nakayiwa, Florence Mayega (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
As part of the AICCRA, the Regional Universities Forum for Capacity Building in Agriculture (RUFORUM) are tasked to develop curricula and training materials to accelerate the mainstreaming of Climate Information Services (CIS) and Climate- Smart Agriculture (CSA) into University’s curricula in Africa. This report describes the activities of a training of trainers’ (ToT) workshop on soil nutrient and water management in crop production course module, held from 28 February to 03 March 2023. The overall objective of the training of trainers’ workshop was to increase awareness and scale adoption/integration of the module on soil nutrient and water management in crop production across the RUFORUM Network and other non-AICCRA countries. 158 (Male=126; Female=32) participants from 81 universities in 26 countries attended the training. The training increased awareness of soil nutrient and water management in crop production among academic staff in RUFORUM member universities. Participants indicated their interest in incorporating the training material into their university curricula.